2006
DOI: 10.1111/j.1600-6143.2006.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Without Prior Dialysis in Children: The Eurotransplant Experience

Abstract: Kidney transplantation without prior dialysis may prevent dialysis-associated morbidity. We analyzed the outcome of 1113 first kidney transplants in children performed between 1990 and 2000 in the Eurotransplant community. Enlistment for a deceased donor kidney before start of dialysis (127/895, 14%) made dialysis redundant in 55% of cases. Mean residual creatinine clearance at transplantation of these patients was 8 mL/min/1.73 m 2 . Pre-emptive transplantations of deceased donor kidneys showed less acute rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 31 publications
2
59
2
3
Order By: Relevance
“…We hypothesize that patients who have a suitable donor are likely to have their transplant timed early enough to avoid dialysis [21] and therefore at a higher GFR than that at which they would commence dialysis. Nevertheless, a previous study found no differences in eGFR levels between pre-emptive and post-dialysis transplant patients [13]. However, their eGFR levels were much lower than those reported in our study.…”
Section: Treatment Modalitycontrasting
confidence: 98%
See 1 more Smart Citation
“…We hypothesize that patients who have a suitable donor are likely to have their transplant timed early enough to avoid dialysis [21] and therefore at a higher GFR than that at which they would commence dialysis. Nevertheless, a previous study found no differences in eGFR levels between pre-emptive and post-dialysis transplant patients [13]. However, their eGFR levels were much lower than those reported in our study.…”
Section: Treatment Modalitycontrasting
confidence: 98%
“…The main determinants of eGFR at start were age, gender, treatment modality at start as well as time between the first visit to a PN and start of RRT. We found slightly higher median eGFR levels at start compared with US dialysis patients [5,12] and patients from the Eurotransplant registry [13]. However, these studies took place at an earlier period in slightly younger patients.…”
Section: Discussionmentioning
confidence: 57%
“…A younger age at the start of RRT, especially for infants who are younger than 1 yr, has been a risk factor for mortality (15,16,20); however, early transplantation, in particular preemptive transplantation, has been shown to improve survival and reduce mortality in children who have CRF and are younger than 5 yr (7,22). Patients who underwent preemptive RTx showed better graft survival (23), probably because the donor was living related and because of shorter cold ischemia time (24). Survival of infants who underwent RTx was comparable to that of older children.…”
Section: Discussionmentioning
confidence: 99%
“…According to a NAPRTCS report from the US, a living donor (LD) kidney was used in about 50 % of all pediatric RTx and in 74 % of infant RTx [5]. In the Eurotransplant region, the percentage of LD in pediatric RTx was much less (20 %), but no exact figures were available for infant RTx [16]. The use of either of the parents as an LD brings several advantages: timing of the operation is feasible, RTx can be performed pre-emptively, immunological matching is at least satisfactory (one haplotype), the donor age is often low (<35 years), and the cold-ischemia time is very short.…”
Section: Donor Characteristicsmentioning
confidence: 99%